Diagnostics in cystic echinococcosis: Serology versus ultrasonography - Wuestenberg, Johanna; Gruener, Beate; Oeztuerk, Suemeyra; A. Mason, Richard; M. Haenle, Mark; Graeter, Tilmann; S. Akinli, Atilla; Kern, Peter; Kratzer, Wolfgang (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Cystic echinococcosis (CE) is the most widespread zoonosis worldwide. The objective of the present study was to compare diagnostic methods in the work-up of suspected cystic echinococcosis of the liver. Materials and Methods: Data from a total of 68 patients were compiled and analyzed. Results: A diagnosis of cystic echinococcosis was made in 36.8% of patients. Broken down according to WHO criteria, patients with at least one echinococcus cyst were determined in 12.0% of cases to exhibit cysts consistent with stage 1 disease (CE1), while in 24.0%, cysts consistent with CE2 and CE3 were identified. CE4 and CE5 cysts were identified in 32.0% and 8.0% of patients, respectively. Solitary cysts were found in 60.0% of patients with cystic echinococcosis, while in patients with at least one cystic lesion, there were most often multiple cysts. The indirect hemagglutination test (IHA) and echinococcus-specific immunoglobulin E (IgE) concentration showed a higher sensitivity (60.9%, 68.4%) than did the enzyme-linked immunosorbent assay (ELISA) for Echinococcus multilocularis (Em2+) and total IgE (11.1%, 38.9%). The respective specificities of all four serological methods lay between 83.9% and 88.9%. Conclusion: Our data show that ultrasound remains the diagnostic method of choice in the work-up of cystic lesions of the liver suspected to be due to Echinococcus granulosus. Serological methods can serve an adjunctive role.